P23 The incidence of congenital thoracic malformations: an increasing trend from 1994 to 2011 in a defined population. (14th November 2013) - Gorman, EA; Thavagnanam, S; Houton, J; Dick, A; Patterson, A; Shields, MD
Abstract : Introduction: Congenital thoracic malformations (CTMs) are an uncommon heterogenous group of disorders including congenital cystic adenomatous malformation (CCAM), pulmonary sequestration (PS), congenital lobar overinflation (CLO), hybrid lesions and bronchogenic cysts. They are increasingly diagnosed antenatally with foetal ultrasonography and remain asymptomatic. In light of diagnostic advances, robust population based epidemiology is lacking. This study aimed to characterise the incidence of CTMs in a defined geographic area from 1994 to 2011. Methods: Children with CTM in Northern Ireland are referred to a single tertiary centre. Patients with CTM born between 1994 and 2011 were identified from the paediatric respiratory and surgical clinics and from imaging reports on the regional radiology database. Medical records and imaging reports were reviewed retrospectively. Children diagnosed with CTM who were born outside of Northern Ireland were excluded. All births in Northern Ireland are registered with the Registrar General Office. Annual live birth rates were obtained from the Northern Ireland Statistics and Research Agency. Incidence was calculated per 10000 live births. Results: In total there were 92 cases of CTM between 1994 and 2011, 53 cases (57%) had CCAM. An upward trend in the incidence of CTMs is demonstrated (Figure 1 ). The average incidence of CTMs from 1994 to 1999, 2000 to 2005 and 2006 to 2011 was 0.49 (range 0.41 to 0.82), 1.6 (range 0.89 to 1.85) 4.08 (range 2.34 to 7.73) respectively. A similar increase in the incidence of CCAM was demonstrated 0.14 (range 0to 0.42), 1.22 (range 0.93 to 1.40) and 2.19 (range 0.39 to 5.59) for the periods 1994 to 1999, 2000 to 2005 and 2006 to 2011 respectively. Conclusion: This study provides incidence statistics for CTMs in a defined geographic location and demonstrates an increasing incidence between 1994 and 2011, likely due to advances in antenatal diagnosis. The retrospective nature of this study means that patients with CTM who were not followed up postnatally and not imaged postnatally would not be included. The incidence provided therefore represents the minimum incidence. The increasing incidence of CTMs has therapeutic implications as the complication rates may be lower than previously repoted.